Urachal fibrous band unveiled by a red umbilical papule. - Avhad, G.; Jerajani, H.R. (European Journal of Pediatric Dermatology, 2011)
Case report. A 5-year-old boy was affected since birth by a red umbilical papule associated with intermittent pain and discharge of clear fluid. There was also history of bleeding with trauma or spontaneously. His mother denied any history of pus discharge, infection of umbilical stump or trauma at birth. The cutaneous examination revealed a 5 mm in diameter solitary, well circumscribed, bright red, sessile papule, with smooth surface on the umbilicus (Fig. 1). There was no lymphadenopathy. Complete hemogram, chemistry profile and bacteriological culture were normal or negative. Ultrasonography of the lesion showed a linear anechoic lesion, extending for 7.3 cm below the umbilicus and reminiscent of a sinus tract ( Figure 2). On surgical operation (Fig. 4) the sinus tract proved to be connected with the dome bladder. The histological examination of the excised tissue measuring 3.5cm x 0.4cm x 0.2cm (Fig. 3) showed a fibrous band. The clinical, ultrasonographic, surgical and histological findings led to the final diagnosis of urachal fibrous band. There were no postoperative complications or recurrences after treatment.